Kebijakan Antidumping Dalam Rangka Meningkatkan Pertumbuhan Ekonomi Di Masa Pasca Pandemi - Primadhany, Erry Fitrya; Angraeni, Novita; Ihsan, Reza Noor; Rahman, Akmal Anshari (Pusat Riset dan Inovasi Nasional, 2024)
Abstract. The global economy has faced a decline during the pandemic, leading to substantial barriers in international trade. Governments in various countries have implemented policies to protect their domestic markets, including measures to avoid dumping practices. Indonesia experienced instances of dumping practices during the pandemic. Therefore, it is crucial to review government policies as regulators to safeguard domestic products and promote economic growth post-pandemic while avoiding dumping accusations. This research adopts a normative approach with a legal research method of literature. The study employs a statutory approach and a conceptual approach to analyze the subject matter. The findings of this research indicate that antidumping policies are enshrined in various provisions, including Laws and Government Regulations governing the imposition of Antidumping Duties. To foster economic growth in the post-pandemic era, post-pandemic antidumping policies need to consider several aspects. The government should conduct a thorough analysis and evaluate the synchronization of international trade institutions with WTO and other countries oriented towards economic growth. Additionally, enhancing cooperation between stakeholders and institutions related to international trade, such as the KADI, is essential. The government can also take preventive measures by engaging in effective communication with exporters and importers to improve product quality and enhance their understanding of international trade, particularly concerning dumping practices. Keywords: International Trade Policy, Dumping Practices, Economic Growth, Post-Pandemic Era Abstrak. Ekonomi global telah mengalami penurunan selama pandemi, yang mengakibatkan hambatan substansial dalam perdagangan internasional. Pemerintah di berbagai negara telah menerapkan kebijakan untuk melindungi pasar domestik mereka, termasuk langkah-langkah untuk menghindari praktik dumping. Indonesia mengalami beberapa praktik dumping selama pandemi. Oleh karena itu, sangat penting untuk meninjau kebijakan pemerintah sebagai regulator untuk melindungi produk dalam negeri dan mendorong pertumbuhan ekonomi pascapandemi sambil menghindari tuduhan dumping. Penelitian ini mengadopsi pendekatan normatif dengan metode penelitian hukum berbasis literatur. Studi ini menggunakan pendekatan undang-undang dan pendekatan konseptual untuk menganalisis pokok permasalahan. Temuan penelitian ini menunjukkan bahwa kebijakan antidumping diatur dalam berbagai ketentuan, termasuk Undang-Undang dan Peraturan Pemerintah yang mengatur pengenaan Bea Masuk Antidumping. Untuk mendorong pertumbuhan ekonomi di era pascapandemi, kebijakan antidumping pascapandemi perlu mempertimbangkan beberapa aspek. Pemerintah harus melakukan analisis mendalam dan mengevaluasi sinkronisasi lembaga perdagangan internasional dengan WTO dan negara-negara lain yang berorientasi pada pertumbuhan ekonomi. Selain itu, meningkatkan kerjasama antara pemangku kepentingan dan lembaga terkait perdagangan internasional, seperti KADI, sangat penting. Pemerintah juga dapat mengambil langkah-langkah preventif dengan berkomunikasi efektif dengan eksportir dan importir untuk meningkatkan kualitas produk dan pemahaman mereka tentang perdagangan internasional, terutama mengenai praktik dumping. Kata kunci: Kebijakan Perdagangan Internasional, Praktik Dumping, Pertumbuhan Ekonomi, Masa Pascapandemi